2010
DOI: 10.5424/fs/2010192-01320
|View full text |Cite
|
Sign up to set email alerts
|

The efforts for cork oak forest management and their effects on soil conservation

Abstract: The Shoul oak grove is a forested ecosystem inherited from a Holocene phase of ecological optimum; its evolution, through the double geologic and human temporality, and in relation with several processes of degradation, led to the progressive loss of its environmental equilibrium and further to the reduction of its economic contributions. The fragility of these forests is the consequence of the convergence of two main factors, i) the intrinsic fragility of the forested environment based on an unstable balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…All these activities have created areas of open degraded land (Oubrahim et al 2016). In addition to woodland degradation, the surface area of native forests has diminished because of conversion to croplands that are dedicated to local food supply (Laouina et al 2010). To cope with this situation, the Moroccan State initiated several plans aiming at restoring forest ecosystems, or just soil fertility (Laouina et al 2010;Oubrahim 2015).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…All these activities have created areas of open degraded land (Oubrahim et al 2016). In addition to woodland degradation, the surface area of native forests has diminished because of conversion to croplands that are dedicated to local food supply (Laouina et al 2010). To cope with this situation, the Moroccan State initiated several plans aiming at restoring forest ecosystems, or just soil fertility (Laouina et al 2010;Oubrahim 2015).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…These rural pressures, combined with more frequently occurring water stress in drought periods and insect attacks (El-Badri & Abadie 2000, Lumaret et al 2005, Ghaioule et al 2007) have led to a degradation of the cork oak ecosystem. In addition to rural pressures, the cork oak forest of Mamora is influenced by several surrounding cities, thereby exposing the forest to leisure activities as well as uncontrolled urbanization (Laouina et al 2010). As a result of all these factors of forest degradation and regression, the specific composition of the forest is disturbed, recruitment of new saplings has become almost impossible (Benabid 2000), and its surface area has greatly decreased over the last century (Aafi 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The main problems of degradation as identified by the local stakeholders during the first workshop included the following 20 : Delayed precipitation in autumn and early dryness in spring led to a decrease in water availability, a shorter growing season, and a reduction of grain yields and vegetation cover.Intense and heavy rainfall in autumn, at a time when the soil is completely bare, caused severe soil erosion.Overexploitation of wells and increased runoff on the fields caused the water table to decline.The vegetation cover was reduced and degraded inside the forest as well, and cork oak degraded beyond regeneration.The participatory process revealed that farmers in Sehoul are primarily interested in animal husbandry. For this reason, for example, crop residues compete with fodder, and cover management is only an option in years with sufficient biomass production; otherwise any plant biomass is completely used up for the animals.…”
Section: Resultsmentioning
confidence: 99%
“…Data gathered during the participatory process consisted of workshop reports 19 , 20 ; semi-structured interviews with ten stakeholders conducted in order to analyze the overall three-part methodology (as described in Schwilch et al 18 ); numerous conversations with farmers, technicians and researchers during field visits and meetings at administrative offices; participatory observation during stakeholder workshops and field trials; DESIRE project documents (posters at meetings, annual reports, etc. ); and WOCAT questionnaires filled in after trial implementation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation